Optimal allocation of distribution generator in a radial-distribution system using self-adaptive modified firefly algorithm with voltage, power and line capacity limit constraints. (2015) - Saha, Sanjoy Kumar; Banerjee, Sumit; Chanda, Chandan Kumar
As a result of the application of deregulation in the electric power sector, a new identity appeared in the electric power system map known as 'distribution generator' (DG). To meet out the peak load demand caused by increased power demand in the distribution system, DGs are greatly utilised by placing DGs in optimal location with optimal size. This paper presents a novel firefly optimisation-based approach to optimally incorporate a distribution generator into a distribution system. The proposed algorithm combines firefly optimisation with load flow algorithm to solve the problem in a single step. While developing the algorithm, by satisfying the voltage, power and line capacity limit, the objective function, i.e., the total network power losses will be minimised. Loss sensitivity factors (LSFs) are used to select the location for the multiple DG placements and self-adaptive modified firefly algorithm (SAMFA) is used to estimate the optimal size of DGs at optimal locations determined. Taking the self-adaptive modified firefly algorithm (SAMFA) and IEEE 69-node system as the example, the results show the effectiveness of the proposed algorithm.